Romanian theology: A theology of dialogue - Chirilă, Ioan (HTS teologiese studies, 2009)
This article offers an overview of the development of Romanian theology through the 20th century, especially after 1989, which constituted a new era for the evolution of Romanian theology. The author believes that the greatest challenge for the Romanian Orthodox Church after 1989 is the one that aims at the reconfiguration of the mission of the Christian martyria within the new forms of religious and social freedom. The author states the necessity for Romanian theology for its own katharsis (purification) as well as the necessity for eliminating the idea that between theology and the other sciences there is a relationship of antinomy. The author firmly states his credo as a theologian, namely the theological theme of deification/theosis, understood either in the way of Saint Paul as ‘gods through grace’ or in the way of Saint Peter as ‘partakers of the divine nature’: homo-Deus.